EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS IN GOVERNMENT UNITS IN AL-QADISIYAH GOVERNORATE FROM THE MANAGEMENT'S POINT OF VIEW - Muayad Abdulameer Habeeb; Ihsan Abdulhamza Khamees; Wijdan Mohammed Alwan (Scholar Express Journals, 2022)
Study Objective: To identify the concept and components of accounting information systems in government units and to identify the effectiveness of accounting information systems in government units in meeting the Department's requirements to carry out its functions of planning, controlling and making decisions. Study found: The planning and oversight function is interrelated, since planning is a preliminary assessment of alternatives in order to choose their preferences with a view to achieving good oversight. The latter helps to track actual implementation and compares it with planned performance. Accounting information is one of the main pillars of the Integrated DecisionMaking System in government units in Qadisiyah governorate. Study recommended: Attention should be paid to the planning of the financial and human resources of the government units in Qadisiyah governorate, which will increase the efficiency and effectiveness of the planning process in those units and the success of the planning process, and the need to pay attention to the supervisory aspect of the government units in Qadisiyah governorate, which works to diagnose deviations and errors and work to correct them in order to reach appropriate decisions.
Keywords: Accounting Information Systems; Government Units